Analisis Pemulihan Korban Tindak Pidana Terorisme di Badan Nasional Penanggulangan Terorisme - Hambali Ivan Elzabilillah; Untung Sumarwan (Universitas Budi Luhur, 2022)
This study discusses the role of the National Counterterrorism Agency in the Protection of Victims of Criminal Acts of Terrorism, especially victims of past terrorism. This study uses a conceptual analysis of victim recovery where reparation is a mechanism for victim recovery carried out by the State as a form of acknowledgment of violations against victims, loss and suffering experienced by victims. The research subjects admitted that the victims felt very helped from the repairs, because it really helped the victims from an economic and medical point of view. In this study, the researcher used a qualitative approach method by finding out information directly with informants and information to obtain data and facts needed to find out the analysis contained in this problem. The results of this study are an analysis of the role of the National Counterterrorism Agency in the Protection of Victims of Terrorism Crime is to determine the status of victims as victims of criminal acts of terrorism, also formulate national strategic policies and programs in the field of counter terrorism, coordinate relevant government agencies in implementing and implementing policies in the field of counter terrorism.